Difluorodithieno[3, 2-a:2′, 3′-c]phenazine as a strong acceptor for materials displaying thermally activated delayed fluorescence or room temperature phosphorescence. (June 2021) - Cardeynaels, Tom; Paredis, Simon; Danos, Andrew; Harrison, Alastair; Deckers, Jasper; Brebels, Sonny; Lutsen, Laurence; Vanderzande, Dirk; Monkman, Andrew P.; Champagne, Benoît; Maes, Wouter
Abstract: A novel strong electron-acceptor unit, 9, 10-difluorodithieno[3, 2- a :2′, 3′- c ]phenazine (DTPz), is synthesized and applied in the design of two donor-acceptor type emitters displaying long-lived delayed emission. Using either 9, 9-dimethyl-9, 10-dihydroacridine (DMAC) or triisopropyl-substituted benzo[1, 2- b :4, 5- b' ]dithiophene (BDT-TIPS) as the donor component, push-pull type chromophores exhibiting charge-transfer emission are obtained and found to afford either thermally activated delayed fluorescence (TADF) for DMAC or room temperature phosphorescence (RTP) for BDT-TIPS. Graphical abstract: Image 1 Highlights: Difluorodithieno[3, 2- a :2′, 3′- c ]phenazine (DTPz) is applied as acceptor in TADF materials. The time-resolved photophysical properties are studied. Quantum-chemical analysis is used to estimate the charge-transfer character. Different emission mechanisms are found (TADF vs RTP). Room temperature phosphorescence occurs from a local DTPz state.